Myelopathy as the first manifestation of AIDS - Yuanyuan Li; Qianru Yang; Hong Lin; Qiong Zhou; Fangfang Ge; Jiankuan Shi (AIDS Research and Therapy)
Abstract Background Human immunodeficiency virus (HIV) is a retrovirus mainly infecting immune cells. Central nervous system diseases in HIV-infected patients can be caused by HIV or opportunistic infections. Neurological diseases associated with HIV have diverse manifestations and may occur in early or late stages. This article reports an HIV patient with myelopathy as initial symptom and negative spinal cord magnetic resonance imaging (MRI) and reviews common classifications of HIV-related spinal cord diseases. Case presentation A 50-year-old male presented with weakness in both lower limbs and gait disorders for more than three months. Physical examination and various tests ruled out many possible causes. Given positive HIV and syphilis antibody in serological examination, normal spinal cord MRI and electromyogram, and after excluding other potential diagnoses through comprehensive analysis, the diagnosis of HIV-related myelopathy was established. Conclusions Spinal cord lesions caused by HIV infection involve multiple aspects in terms of etiology and mechanism. HIV infection-related vacuolar myelopathy (HIV-VM) is the most common and typical spinal cord lesion. It usually appears at a relatively late stage of HIV infection, but it may also occur in the early stage and even serve as the initial manifestation of newly diagnosed HIV. The diagnosis of HIV myelopathy is usually exclusionary. In imaging, it often shows high T2 signal and spinal cord atrophy on spinal cord MRI, or it may also appear normal. Clinical Trial Not applicable.